2023
DOI: 10.1037/met0000608
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intra- and inter-individual reliabilities in intensive longitudinal studies: A two-level random dynamic model-based approach.

Abstract: Intensive longitudinal studies are becoming increasingly popular because of their potential for studying the individual dynamics of psychological processes. However, measures used in such studies are quite susceptible to measurement error due to the short lengths and therefore their psychometric properties, such as reliability, are of great concern. Most existing approaches for assessing reliability are not appropriate for the intensive longitudinal data (ILD) because of the conflation of inter- and intra-indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…For example, it has recently been suggested to estimate both between-and within-person reliabilities using a two-level random dynamic measurement model (Xiao, Wang, & Liu, 2023). Moreover, latent Markov factor analysis can be used to probe intrapersonal changes in measurement models over time or situations (Vogelsmeier, Vermunt, van Roekel, & De Roover, 2019).…”
Section: Alternative Approaches and Possible Extensionsmentioning
confidence: 99%
“…For example, it has recently been suggested to estimate both between-and within-person reliabilities using a two-level random dynamic measurement model (Xiao, Wang, & Liu, 2023). Moreover, latent Markov factor analysis can be used to probe intrapersonal changes in measurement models over time or situations (Vogelsmeier, Vermunt, van Roekel, & De Roover, 2019).…”
Section: Alternative Approaches and Possible Extensionsmentioning
confidence: 99%
“…To the best of our knowledge, these approaches include: (a) The generalizability theory (Cranford et al, 2006), (b) the multilevel framework (Nezlek, 2017), (c) the multilevel confirmatory factor analysis model (Geldhof et al, 2014;Lai, 2021), (d) the dynamic factor analysis approach (Fuller-Tyszkiewicz et al, 2017;Hu et al, 2016), (e) the latent state-trait theory (Castro-Alvarez et al, 2022), and (f) the DSEM framework (Xiao et al, 2023). Nevertheless, approaches that estimate the test-retest reliability of intensive longitudinal data have also been proposed for single-item measures, such as the multilevel (vector) autoregressive model with measurement error (Schuurman & Hamaker, 2019), and the test-retest reliability coefficients for experience sampling methods suggested by Dejonckheere et al (2022).…”
Section: Intensive Longitudinal Datamentioning
confidence: 99%
“…In our review of the literature, we identified three approaches to estimate the reliability of intensive longitudinal data that are fairly known and used by empirical researchers: The generalizability theory (Cranford et al, 2006), multilevel modeling (Nezlek, 2017), and multilevel confirmatory factor analysis (Geldhof et al, 2014;Lai, 2021). Additionally, we identified three novel approaches that have not been applied in empirical studies: The dynamic factor analysis approach (Fuller-Tyszkiewicz et al, 2017;Hu et al, 2016), the latent state-trait theory (Castro-Alvarez et al, 2022), and the two-level random dynamic model-based approach (Xiao et al, 2023). All of these approaches have in common that they allow for estimating the reliability of the scales used in intensive longitudinal research when several items are repeatedly administered to measure one construct (e.g., using the items energetic, happy, and enthusiastic to measure positive affect).…”
Section: Reliability Estimates For Intensive Longitudinal Datamentioning
confidence: 99%
See 2 more Smart Citations